Generalized John Gromov hyperbolic domains and extensions of maps - Zhou, Qingshan; Li, Liulan; Rasila, Antti (MATHEMATICA SCANDINAVICA, 2021)
Let Ω R^n be a Gromov hyperbolic, φ-length John domain. We show that there is a uniformly continuous identification between the inner boundary of Ω and the Gromov boundary endowed with a visual metric, By using this result, we prove the boundary continuity not only for quasiconformal homeomorphisms, but also for more generally rough quasi-isometries between the domains equipped with the quasihyperbolic metrics.